Auditoria financiera a las cuentas por cobrar (cartera crédito) de la empresa CHP Materiales para Construcción S.A. del 01 de enero al 30 de junio de 2012 en Girón, Santander (2012)
Conduct of the audit to the portfolio company credit checking balances, confirming the portfolio and proposing improvement actions regarding the indicators from the Treasury to improve monitoring and enforcement of the indicators proposed by management of the company. This audit was applied to customers whose portfolio exceeded the amount of 10 million, and that the company's management clients are more representative of the company for which the test sample is the most reliable possible. For the realization of this audit was carried out implementation of internal control questionnaire, analysis of portfolio turnover; profiling each position from the Treasury and portfolio and finally implementing a daily collection budget with which to measure compliance department in monitoring portfolio to customers and the cash payment schedule.